Про один клас інтегро-диференціальних операторних рівнянь відносно узагальненого диференціювання Гельфонда–Леонтьєва - Лінчук, Ю.С. (Видавничий дім "Академперіодика" НАН України, 2008)
We describe solutions of a class of integro-differential operator equations which contain the generalized differentiation and integration. An analog of Delsartes–Lions’s formula for the representation of solutions of such equations is obtained.